Diarrhea with encephalopathy: A case report - Hale, Katherine; Rampersad, Neeta; Elliott, Elizabeth (Journal of Pediatric Infectious Diseases, 2007)
We report a case of Salmonella typhimurium encephalopathy in a 7-year-old girl. The patient presented with abrupt onset of coma following a brief history of diarrhea, vomiting and fever. Despite aggressive and appropriate management, she developed acute renal failure and coagulopathy and irreversible neurological compromise. No adequate alternative explanation was found for her disease. A summary of published cases is presented and postulated pathogenic mechanisms are discussed, which includes an endotoxin triggered inflammatory response.
Keywords: Salmonella infections; Salmonella typhimurium; brain diseases